Rice Seedling Resistance due to Seed Priming and Seeding Density under Submergence Stress Condition - Sulaiman, Firdaus; Agus Suwignyo, Rujito; Hasmeda, Mery; Wijaya, Andi; Irmawati, Irmawati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
The study of rice seedling resistance due to seed priming and seeding density under submergence stress condition was carried out to evaluate the effect of seed priming and also to estimate proper seeding population density to improve rice seedlings vigor under submergence stress condition. The เว็บสล็อต | R4shub experiment was conducted in tidal freshwater swamp of Sako in Rambutan District, Banyuasin Regency (3.067° S, 104.8616° E). Randomized block design was used where the seeds were soaked into ZnSO4.7H2O solution as priming treatment, and then sown with three different seeding rates: 30, 40 and 50 kg ha-1. Three cultivars consisted of Inpara 3, Inpara 5 and Ciherang were tested. The observation was carried out until 4 weeks after sowing to measure the seedling height, shoot dry weight, carbohydrate content in stem, and leaf chlorophyll. Results showed that all treatments indicated insignificant effect to all parameters. However, the highest result from all parameters was obtained from priming treatment. The higher seeding density the lower dry weight, carbohydrate and chlorophyll content. All three tested cultivars, Inpara 3 gave the best performance.